Surveillance of surgical site infections after gastrointestinal surgery in the south region of the Netherlands - Ramcharan, Amita; Smeets, Ed; Rouflart, Margriet; Tiel, van, Frank; Bruggeman, Cathrien; Breukink, Stéphanie; Tordoir, Jan; Baeten, Cor (International Journal of Infection Control, 2014)
A surgical site infection (SSI) is a serious and costly complication with the highest rates being reported after gastrointestinal surgery. The objective of this cross sectional study was to assess the incidence and risk factors of SSI after gastrointestinal surgery during and after hospitalization, and to evaluate the effect of the VMS (Dutch: “VeiligheidsManagementSysteem”) safety programme on the SSI rate. We assessed the SSI rate from July 2008 until December 2011, according to the criteria of the Centers for Disease Control and Prevention (CDC), before and after implementation of the VMS safety programme which includes a bundle of four interventions. We differentiated between the SSI rate during and after hospitalization and between superficial, deep and organ/space infections. The incidence of SSI in relation to the wound class, risk factors for SSI, and the compliance with the programme were assessed. Data were obtained during a thirty-day follow-up period after surgery. Surveillance after discharge significantly increased the overall SSI rate. Age higher than fifty years and contaminated or dirty wounds were risk factors for SSIs. Despite increased compliance with the safety programme, no significant decrease in SSI rate was found after implementation. The Dutch VMS safety programme did not show a significant effect on the decrease in incidence of SSI. Surveillance during and after hospitalization is essential for a reliable assessment of the SSI rate.